Penggunaan Platform Online dalam Pengajaran Matakuliah Al-Hadis dalam Bahasa Arab - Burhanuddin, Burhanuddin; Lailawati, Lailawati (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
The use of online platforms in teaching Al-Hadith courses in Arabic is the focus of this study, which aims to evaluate the effectiveness of technology-based learning in the pandemic era. This study uses a qualitative approach with a purposive sampling method in the Islamic Broadcasting Communication Study Program, Faculty of Da'wah and Communication Sciences UIN Syarif Hidayatullah Jakarta, involving 33 2nd semester students. Data were collected through online questionnaires, with 8 questions using a Likert scale 5 to measure student perceptions. Data analysis follows the Miles and Huberman model through data reduction, presentation, and inference. The results showed that most students felt technically ready to use online platforms, facilitating in-depth interactions such as discussions and forums. Support from teachers and time flexibility have also been shown to increase student satisfaction with learning. However, challenges in time management and the need for active involvement of teachers were also identified as important factors. In conclusion, learning al-Hadith through online platforms can provide an effective and satisfying learning experience, provided there is adequate infrastructure and support.